HPK1 associates with SKAP-HOM to negatively regulate Rap1-mediated B-lymphocyte adhesion. - Sebastian Königsberger (Public Library of Science (PLoS), 2010)
Background Hematopoietic progenitor kinase 1 (HPK1) is a Ste20-related serine/threonine kinase activated by a range of environmental stimuli including genotoxic stress, growth factors, inflammatory cytokines and antigen receptor triggering. Being inducibly recruited to membrane-proximal signalling scaffolds to regulate NFAT, AP-1 and NFkappaB-mediated gene transcription in T-cells, the function of HPK1 in B-cells to date remains rather ill-defined. Methodology/principal findings By using two loss of function models, we show that HPK1 displays a novel function in regulating B-cell integrin activity. Wehi 231 lymphoma cells lacking HPK1 after shRNA mediated knockdown exhibit increased basic activation levels of Ras-related protein 1 (Rap1), accompanied by a severe lymphocyte function-associated antigen-1 (LFA-1) dependent homotypic aggregation and increased adhesion to intercellular adhesion molecule 1 (ICAM-1). The observed phenotype of enhanced integrin activity is caused downstream of Src, by a signalling module independent of PI3K and PLC, involving HPK1, SKAP55 homologue (SKAP-HOM) and Rap1-GTP-interacting adaptor molecule (RIAM). This alters actin dynamics and renders focal adhesion kinase (FAK) constitutively phosphorylated. Bone marrow and splenic B-cell development of HPK1(-/-) mice are largely unaffected, except age-related tendencies for increased splenic cellularity and BCR downregulation. In addition, naïve splenic knockout B-cells appear hyperresponsive to a range of stimuli applied ex vivo as recently demonstrated by others for T-cells. Conclusions/significance We therefore conclude that HPK1 exhibits a dual function in B-cells by negatively regulating integrin activity and controlling cellular activation, which makes it an interesting candidate to study in pathological settings like autoimmunity and cancer.